The Role of Systems Thinking in Systems Engineering, Design and Management - Weng Tat Chan (Institute of Research and Community Outreach - Petra Christian University, 2015)
Systems thinking is a widely recognized and subscribed-to concept. Many benefits are ascribed to systems thinking and its result - the holistic solution. Yet, there is a wide range of opinion as to what systems thinking really is, and how its benefits can be realized in engineering practice. In fact, the concept of what constitutes a ‘system’ is wide and variable. The purpose of the paper is to draw together diverse perspectives of systems thinking useful in engineering, and to present a set of core concepts that are useful in the successful design and operation of engineered systems. These concepts will be illustrated with examples drawn from the author’s experience in teaching and research on engineered systems.